Development of a new broad-spectrum microencapsulation-based spray drying formulation of Bacillus thuringiensis subsp. kurstaki IMBL-B9 for the control of moths - Duraisamy, Kalaiselvi; Yu, Nan Hee; Kim, Seon Hwa; Baek, Jong Hwi; Son, Ji Yeon; Choi, Euna; Park, Min Gu; Kim, Jiwon; Choi, Jae Young; Sang, Mee Kyung; Je, Yeon Ho; Kim, Jin-Cheol (Frontiers in Microbiology, 2023)
Certain Bacillus thuringiensis (Bt) strains such as Bt subsp. kurstaki and Bt subsp. aizawai have been widely used for pest management in agricultural practices. However, each strain only shows high specificity for pest control against a narrow range of lepidopteran species, and numerous lepidopteran pests have developed resistance to commercialized Bt strains. Therefore, there is a need for the development of novel Bt bioinsecticides which allow for potent and broadspectrum insecticidal activity against lepidopteran species, including Spodoptera spp. (Noctuidae) and Plutella xylostealla (Plutellidae). In order to develop a novel bioinsecticide using Bt subsp.kurstaki IMBL-B9 (Btk IMBL-B9) that exhibits excellent insecticidal activity against three different lepidopteran species, we have developed a viable microencapsulation-based spray drying Btk IMBL-B9 formulation. The spore-crystal complex of Btk IMBL-B9 was microencapsulated using coating materials such as gum arabic, maltodextrin, and corn starch via spray drying. The encapsulated formulation of Btk IMBL-B9 presented an increased survival rate and storage stability at 54±2°C for up to 6 weeks. The formulation showed similar insecticidal activity as the commercial bioinsecticide XenTari® against P. xylostella. Under controlled greenhouse conditions, the Btk IMBL-B9 formulation was more effective against Lepidoptera spp. S. frugiperda and P. xylostella , than XenTari® . These results suggest that the microencapsulationbased spray drying formulation of Btk IMBL-B9 can be used effectively for the control of a wide range of moths.